The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cells9020398
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of circRNA, miRNA, and piRNA during Early Osteogenic and Chondrogenic Differentiation of Human Mesenchymal Stromal Cells

Abstract: The goal of the present study is to identify the differential expression of circular RNA (circRNA), miRNA, and piwi-interacting RNA (piRNA) after lineage commitment towards osteoand chondrogenesis of human bone marrow mesenchymal stromal cells (hMSCs). The cells were maintained for 7 days in either osteogenic or chondrogenic medium. RNA sequencing was performed to assess the expression of miRNA and piRNA, while RNA hybridization arrays were used to identify which circRNA were differentially expressed. qPCR val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 76 publications
0
34
0
Order By: Relevance
“…Recently several circRNAs, miRNAs and piRNA were differentially expressed after 7 days of chondrogenic and osteogenic induction ( Della Bella et al, 2020 ). This analysis identified 130 up and 97 downregulated circRNAs in chondrogenesis, of which 15 were also identified in osteogenesis.…”
Section: Gene Expression Profile In Chondrogenesis Of Mscmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently several circRNAs, miRNAs and piRNA were differentially expressed after 7 days of chondrogenic and osteogenic induction ( Della Bella et al, 2020 ). This analysis identified 130 up and 97 downregulated circRNAs in chondrogenesis, of which 15 were also identified in osteogenesis.…”
Section: Gene Expression Profile In Chondrogenesis Of Mscmentioning
confidence: 99%
“…Investigating if the expression of these genes were influenced by dexamethasone, a component of both induction media ( Table 1 ), the cells were exposed only to the compound in monolayer or pellet culture. The results indicated that while the expression of FKBP5 was affected by the presence of dexamethasone, FASD2 gene showed no alteration in its levels ( Della Bella et al, 2020 ). FASD2 and FKBP5 were previously identified in chondrogenic induction.…”
Section: Gene Expression Profile In Chondrogenesis Of Mscmentioning
confidence: 99%
See 3 more Smart Citations